Math, asked by kjain1718, 1 year ago

y÷5+((y-3)÷2)=7. Simplify

Answers

Answered by Anonymous
2
Answer:

y \:  \div 5 + ((y - 3) \div 2) = 7 \\  \\ write \: as \: fraction \\  \\  \frac{y}{5}  +  \frac{y - 3}{2}  = 7 \\  \\ lcm = 10 \\  \\ multiply \: both \: sides \: by \: 10 \\  \\ 10 \times  \frac{y}{5}  + 10 \times  \frac{y - 3}{2}  = 10 \times 7 \\  \\ 2 y + 5(y -  3)= 70 \\  \\ 2y + 5y - 15 = 70 \\  \\ 7y - 15 = 70 \\  \\ 7y = 70 + 15 \\  \\ 7y = 85 \\  \\ y =  \frac{85}{7}  \\  \\ y = 12.14


HOPE IT WOULD HELP YOU
Similar questions